Monocyte distribution width (MDW) as a reliable diagnostic biomarker for sepsis in patients with HIV - Jinfeng Sun; Yueming Shao; Rui Jiang; Tangkai Qi; Jingna Xun; Yinzhong Shen; Renfang Zhang; Liu Qian; Xialin Wang; Li Liu; Zhenyan Wang; Jianjun Sun; et al. (Emerging Microbes and Infections)
Sepsis is a leading cause of death among patients with HIV, but early diagnosis remains a challenge. This study evaluates the diagnostic performance of monocyte distribution width (MDW) in detecting sepsis in patients with HIV. A prospective observational study was conducted at Shanghai Public Health Center, involving 488 hospitalized patients with HIV aged 18–65 between December 2022 and August 2023. MDW was measured at admission, and its diagnostic accuracy was compared with Sepsis-3 criteria. Survival rates on day 28 and 90 were also recorded. Additionally, five machine learning (ML) models were tested to enhance diagnostic efficacy. Of 488 subjects, 90 were in the sepsis group and 398 in the control group. MDW showed a diagnostic area under the curve (AUC) of 0.82, comparable to C-reactive protein (CRP) and Procalcitonin (PCT) with AUCs of 0.78 and 0.82, respectively. With a cut-off value of 25.25, MDW had a sensitivity of 0.83 and specificity of 0.76. The positive and negative predictive values were 44% and 95%, respectively. When MDW was combined with platelet count, serum albumin, and hemoglobin in a random forest model, the AUC improved to 0.931. The model achieved a sensitivity of 1.00 and specificity of 0.732. MDW is a useful diagnostic marker for sepsis in patients with HIV, with strong sensitivity and specificity. Combining MDW with other lab markers can further enhance diagnostic accuracy.Trial registration: ClinicalTrials.gov identifier: NCT05036928..